Taxonomy and operational identification of Quaternary species of Spiniferites and related genera. (20th December 2018) - Londeix, Laurent; Zonneveld, Karin; Masure, Edwige
Abstract: In this article, we are proposing an Identification Key for recognition of Quaternary Spiniferites species and some morphologically close Quaternary taxa of some related genera. We summarize the morphological features of 43 taxa (including three subspecies and one variety) based on the original description of the holotypes and sometimes supplemented by our observations. In addition to the Identification Key, we refer to published illustrations that feature both typical and atypical specimens for each taxon. The compilation of this key gave us the opportunity to reconsider some taxonomic concepts, which resulted in two new combinations and an emendation: Hafniasphaera granulata (Mao1989 ) comb. nov., emend. and Hafniasphaera multisphaera (Price and Pospelova2014 ) comb. nov. In addition, we recommend that the names Spiniferites nodosus and Spiniferites pseudofurcatus subsp. obliquus be restricted to their holotype.